Soil collembola on land affected by pyroclastic material of Kelud Volcano, Ngantang Malang - Elly Daru Ika Wilujeng; R Widyastuti; B Tjahjono; Y R Suhardjono (Brawijaya University, 2020)
A study of Collembola on land affected by pyroclastic material of Kelud Volcano, Ngantang Malang was conducted to elucidate the abundance and diversity of soil Collembola in a volcanic environment at various elevations. The study area was divided into two habitats, affected and unaffected by pyroclastic materials at each altitude of 900 m above sea level (asl), 1000 m asl, and 1100 m asl. The research was carried out in June 2019 using a stratified purposive sampling method. Soil Collembola was collected on litter and soil layers using a square frame, length and width of 20 x 20 cm to a depth of 5 cm. Litter and soil layer samples were extracted using Modified Berlese Funnel. Collembola was identified based on morphospecies up to the genus level. Each genus was found only one species, therefore genus was considered as a species. Results of the study showed that soil Collembola on land affected by pyroclastic has 20 species and an abundance of 8790 individuals/m2. In the pyroclastic unaffected areas, were found 33 species and an abundance of 3865 individuals/m2. Entomobrya sp. was dominant in the litter and soil layers of all the study areas. This indicates that Entomobrya sp. is a species that is easy to adapt and has high habitat tolerance.